Inducing Different Brain Injury Levels Using Shock Wave Lithotripsy. (24th April 2018) - Divani, Afshin A.; Salazar, Pascal; Monga, Manoj; Beilman, Greg J.; SantaCruz, Karen S.
Abstract : Objectives: To assess the feasibility of inducing different severities of shock wave (SW)‐induced traumatic brain injury (TBI) using lithotripsy. Methods: Wistar rats (n = 36) were divided into 2 groups: group 1 (n = 20) received 5 SW pulses, and group 2 (n = 16) received 15 SWs pulses. The SW pulses were delivered to the right side of the frontal cortex. Neurologic and behavioral assessments (Garcia test, beam walking, rotarod, and elevated plus maze) were performed at the baseline and at 3, 6, 24, 72, and 168 hours after injury. At day 7 after injury (168 hours), we performed cerebral angiography to assess the presence of cerebral vasospasm and vascular damage due to SW‐induced TBI. At the conclusion of the study, the animals were euthanized to assess damage to brain tissue using an overall histologic severity score. Results: The Garcia score was significantly higher, and the anxiety index (based on the elevated plus maze) was significantly lower in group 1 compared to group 2 ( P < .05). The anxiety index for group 1 returned to the baseline level in a fast nonlinear fashion, whereas the anxiety index for group 2 followed a distinct slow linear reduction. Cerebral angiograms revealed a more severe vasospasm for the animals in group 2 compared to group 1 ( P = .027). We observed a statistically significant difference in the overall histologic severity scores between the groups. The median (interquartile range) overall histologic severity scores for groups 1 and 2 were 3.0 (2.75) and 6.5 (6.0), respectively ( P = .023). Conclusions: We have successfully established different SW‐induced TBI severities in our SW‐induced TBI model by delivering different numbers of SW pulses to brain tissue.